Body mass index increases CD4+ count in HIV/AIDS patients on first-line therapy - Widiyanti, Mirna; Hadi, Moch Irfan; Kumalasari, Mei Lina Fitri; Natalia, Evi Iriani; Purba, Dedi Ananta; Adiningsih, Setyo (Faculty of Medicine, Universitas Trisakti, 2020)
BackgroundThe body mass index (BMI) may contribute somewhat to drug metabolism, thus affecting the efficacy of antiretroviral therapy (ART). CD4+ countsÂ Â in people infected with HIV are essential in determining the stage of the disease, initiation of antiretroviral therapy, opportunistic infections and evaluating treatment outcomes. The aim of this study was to determine the association of BMI and clinical stage with CD4+ counts in HIV patients seeking treatment using first-line antiretroviral therapy (ART).MethodsAn analytic study with a cross-sectional approach was conducted involving 251 HIV/AIDS patients who had received first-line antiretrovirals over six months. BMI, clinical staging according to WHO and CD4 + were collected. Multiple linear regression was used to evaluate the relationship between BMI, clinical stage and CD4+.ResultsAmong the enrolled patients, the median age was 36 years, 135 (55%) of the patients was female, 102 (40.6%) was overweight/obese, 161 (64.1%) was in stage 3 of the disease, and the median CD4+ count was 389 cells/mm3. Multiple linear regression test showed two variables with a significant effect on CD4+ count, namely BMI (B=69.247; 95 % CI : 42.886-95.608) and clinical stage (B=61.590; 28.910-94.270). BMI was the most influencing factor for CD4+ count (Î²=0.307) compared to clinical stage (Î²=0.216). ConclusionsBody mass index was the most influencing factor for CD4 + counts of HIV/AIDS patients. Regular ART can increase CD4+ counts and maintain the health of HIV/AIDS patients.